PENGARUH PENERAPAN MANAJEMEN KONFLIK TERHADAP DISPLIN KERJA PEGAWAI PADA DINAS KOMINFO KOTA BIMA - Muhamad Lutfi (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study focuses on the effect of implementing conflict management on employee discipline at the Communication, Informatics and Statistics Service (KOMINFO) in Bima City. The method used in this study is a survey method with a quantitative approach. The data source for this research were employees of the City of Bima Communication and Informatics Office with a total sample of 52 people. As for the data analysis technique using, simple correlation coefficient analysis, coefficient determination analysis, simple linear regression analysis and hypothesis testing. The results of the research and data processing show that the Conflict Management carried out by the Office of Communication and Information has been implemented very well. This is evidenced by the implementation of Conflict Management programs in managing human resources according to the Collaborating, Competing, Avoiding, Accomodating, Compromissing indicators. Work Discipline carried out by the Ministry of Communication and Informatics has been implemented very well, this is evidenced by the implementation of Conflict Management programs in managing human resources according to the indicators of Frequency of Attendance, Level of Alertness, Obedience to Work Standards, Obedience to Work Regulations, Work Ethics. Conflict Management has a positive and significant effect on Employee Work Discipline, while the effect of Conflict Management on Employee Work Discipline is 11.22% while the side is 88.78% influenced by other factors not examined.